2021
DOI: 10.37637/ab.v4i2.695
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Edible Coatings on Postharvest Quality of Mandarin Orange (Citrus reticulata Blanco)

Abstract: Although Nepal produces a large amount of mandarin it faces huge postharvest losses due to improper postharvest practices. Treating fruits with different edible coatings can minimize postharvest losses. The experiment was carried out in the horticulture lab of Prithu Technical College, Dang, Nepal to evaluate the effects of different edible coating materials on the postharvest quality of mandarin. The experiment was laid in Complete Randomized Design (CRD) with three replications and seven treatments  in each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The TSS was increased after storage in all the treatments that might be due to the conversion of starch and other insoluble carbohydrates into soluble solids ( Barsha et al, 2021). In terms of TSS, 50% paraffin wax was best because it recorded the lowest TSS (10.00 Brix) which indicates the lowest increment in TSS value during storage ( Shahid et al, 2011).…”
Section: Effect Of Edible Coating On Total Soluble Solids (Tss)mentioning
confidence: 93%
See 1 more Smart Citation
“…The TSS was increased after storage in all the treatments that might be due to the conversion of starch and other insoluble carbohydrates into soluble solids ( Barsha et al, 2021). In terms of TSS, 50% paraffin wax was best because it recorded the lowest TSS (10.00 Brix) which indicates the lowest increment in TSS value during storage ( Shahid et al, 2011).…”
Section: Effect Of Edible Coating On Total Soluble Solids (Tss)mentioning
confidence: 93%
“…It is well known that calcium directly affects fruit firmness, the incorporation of calcium in the edible coatng was also proved effective(Dhall Rk, 2013).2.4.4. Effect of edible coating on total soluble solids (TSS)The TSS was increased after storage in all the treatments that might be due to the conversion of starch and other insoluble carbohydrates into soluble solids( Barsha et al, 2021). In terms of TSS, 50% paraffin wax was best because it recorded the lowest TSS (10.00 Brix) which indicates the lowest increment in TSS value during storage( Shahid et al, 2011).…”
mentioning
confidence: 98%
“…The increase in TSS content was lowered in other treatments when compared to the control. Due to the establishment of a physical barrier for transpiration losses and a physical barrier for bacterial growth, the results indicated that 50% paraffin wax along with other edible coatings while storage reported a low level of TSS content when compared to the control 45 .…”
Section: Effect Of Coating On Total Soluble Solids (Tss)mentioning
confidence: 97%
“…The decline in seed quality during the commercial system is due to the seeds that were stored during the storage period often facing sub-optimum conditions, especially relative humidity (RH) even at room temperature (Barsha et al, 2021). Seed vigor is the ability of seeds to germinate normally under sub-optimum conditions.…”
Section: Introductionmentioning
confidence: 99%